Tatwir Wasilah Taqwim Al-Mufradat Bistikhdam QuizWhizzer Li As-Shaf Ats-Tsamin Bi Al-Madrasah Al-Tsanawiyah Al-Islamiyah Al-Hukumiyah 1 Payakumbuh - Emil Wahyu Kurnia; Neli Putri (Universitas Islam Negeri Imam bonjol Padang, 2022)
Technological developments in the twenty first century have an influence on Arabic language education. Therefore, teachers must use technology based evaluation media, especially in vocabulary evaluation. The problem statement in this study is how to develop a vocabulary evaluation media using QuizWhizzer for eight grade in MTsN 1 Payakumbuh ?. This research is a development research with ADDIE model which consist of five steps. Namely : Analysis, Design, Development, Implementation, and Evaluation. However, the researcher limits the development procedure in terms of assessing media based on experts in terms of media and linguists. The results of this study are : First, Needs Analysis includes analysis of the 2013 education curriculum, student books and the forms of test used, analysis of the needs of Arabic teachers and students (they really need the development of this media). Second, Designing a vocabulary evaluation media using quizwhizzer includes writing a grid of questions and writing test questions. Third, Developing a vocabulary evaluation media includes making evaluation media in QuizWhizzer. Fourth, Implementation includes expert verification and product trial to teachers and students. The media and linguist validation result show a “Very Good” rating, which means that QuizWhizzer can be used in vocabulary evaluation for eight grade in MTsN 1 Payakumbuh without correction. Fifth, Evaluation includes product modification and final production.